Penerapan Media Gambar Seri untuk Meningkatkan Kemampuan Membaca dan Menulis Permulaan Siswa Kelas II SD Negeri 01 Pulosari Kebakkramat Tahun 2015/2016 - Hariyati, Meilana (2016)
Classroom action research aims to improve the learning process less optimal. Problems happens in the classroom, especially in learning Indonesian about the low ability to read and write the beginning, this study aims to (1) improve the ability to read and write the beginning of second grade students of SD Negeri 01 Pulosari , (2) improve learning outcomes of students of class II. This type of research is used PTK. The study was conducted during two cycles, each cycle two meetings. Classroom action research conducted in SD Negeri 01 Pulosari Kebakkramat 2016 the number of students 18. Based on the results obtained during the study of prasiklus, the first cycle, the second cycle continues to increase. The results obtained based indicator of the ability to read the beginning: (1) read with attention to punctuation 22.22%, 38.88%, and 72.22% (2) read aloud 16.66%, 44.44% and 88 , 88% (3) The disclosure of word fluency 38.88%, 44.44% and 61.11%. For starters indicator of the ability to write (1) write a sentence begins with a capital letter 27.77%, 50% and 83.33% (2) written with spaces and punctuation are 27.77%, 38.88% and 66.66% ( 3) can write 5-8 words 23.22%, 33.33% and 61.11%. The learning result obtained 63.22%, 68.80% and 76.86%. It can be concluded the application of media image series can improve reading and writing skills as well as the beginning of the learning outcomes of students of class II SD Negeri 01 Pulosari 2016.